A Study on the Potential Demand for Natural Gas as fuel among Taxi Owners in Kota Kinabalu, Sabah - Adzmir bin Abd Rahman; Caroline Geetha Arokiadasan (2017)
The awareness on the benefits of natural gas as environmentally friendly, cheap, quality and convenient to use have an impact on the demand of Natural Gas among consumers. This study aims to identify and examine factors that influence market demand for natural gas among taxi owners in Kota Kinabalu. A total of 200 completed responses were collected in the survey. All respondents are drawn from Taxi owners’ around Kota Kinabalu City. The survey was conducted with the collaboration of Sabah Energy Corporation Sdn. Bhd. (SEC)’s Business Development & Marketing Division and West Coast Taxi Owners’ Association. SEC is a government link companies (GLC) with the main task to spearhead the development of energy particularly natural gas distribution and retailing in the State of Sabah.